IMPROVING THE STUDENTS’ READING COMPREHENSION ACHIEVEMENT IN DESCRIPTIVE TEXT THROUGH TEAM GAMES TOURNAMENT - Desi Yusnanda Sari; Sri Minda Murni (Universitas Negeri Medan, 2014)
This study attempted to improve the students’ reading comprehensionachievement in descriptive text through Team Games Tournament (TGT) method.This study was conducted by using classroom action research. The subject of theresearch was class IX SMP PAB 10 Medan Estate which consisted of 25 students.The research was conducted in two cycles and the first cycle consisted of fourmeetings the second cycle consisted of two meetings. The instruments forcollecting the data were quantitative data (reading evaluation) and qualitative data(diary note, observation sheet and interview sheet). Based on reading scores,students’ score kept improving in every evaluation. In the test I the mean was65,33, in the test II the mean was 71,72 and the test III the mean was 84,54.Basedon diary note, observation sheet and interview sheet, it was found that teachinglearningprocess ran well. Students were active, enthusiastic, and interested inreading. The result of the research showed that Team Games Tournament (TGT)method significantly improved students’ achievement in reading comprehensionespecially in reading descriptive text.